Developing Students’ Learning and Innovation Skills Using the Virtual Smart Classroom - Noawanit Songkram; Nutthakorn Songkram; Suparoek Chootongchai; Thanat Samanakupt (International Journal of Emerging Technologies in Learning (iJET), 2021)
This study examined the development of learning and innovation skills among students in the virtual learning environment provided by the smart classroom which is comprised by three technological components containing (1) virtual 3D classroom created by OpenSimulator, (2) Learning Management System (LMS) created by Moodle and (3) the add-on Moodle’s plug-in, known as INNO ED TOOLs. The new system design which make connection between the virtual 3D classroom and the LMS known as Virtual Smart Learning and Innovation System (VSLI). The VSLI was created in accordance with the principles of constructivism in order to guide and foster creative thinking among learners and enhance their skills in innovation.
Keywords: Technology-Enhanced Education Studies; Online and Blended Learning; Virtual Reality Applications and Impacts